2022
DOI: 10.3390/ijerph192114224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insomnia in the Early Post-COVID-19 Recovery Period

Abstract: Background: Sleep is a complex, reversible process that is responsible for the modulation of various physiological mechanisms. COVID-19-related sleep disorders are affecting different populations with a heterogenous prevalence, yet high rates among infected patients are frequently reported. The aim of the study is to assess the prevalence of insomnia in the early post-COVID-19 recovery period and explore the differences in the results acquired by the Athens Insomnia Scale (AIS) by gender and selected infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…They concluded that the prevalence of insomnia in the early post-COVID19 recovery period was quite high, with one in five having the clinical criteria for the diagnosis. Another important finding was that persistent COVID-19 symptoms were positively correlated with the development of insomnia to a greater extent than the number of symptoms observed in the acute phase of the disease [14]. In our study, we did not include information regarding the persistence of COVID-19 symptoms to verify if there are links between "Long COVID" syndrome and altered sleep quality.…”
Section: Discussionmentioning
confidence: 89%
“…They concluded that the prevalence of insomnia in the early post-COVID19 recovery period was quite high, with one in five having the clinical criteria for the diagnosis. Another important finding was that persistent COVID-19 symptoms were positively correlated with the development of insomnia to a greater extent than the number of symptoms observed in the acute phase of the disease [14]. In our study, we did not include information regarding the persistence of COVID-19 symptoms to verify if there are links between "Long COVID" syndrome and altered sleep quality.…”
Section: Discussionmentioning
confidence: 89%
“…When comparing the AIS results of men and women, the latter scored higher. A significant sex difference was also found when comparing individual questions: women had worse rates of total sleep duration, well-being, physical and mental readiness the following day, and sleepiness during the day [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not find a single risk factor identified by several studies, underlying the need for expanding research on sex differences and insomnia. The risk factors that we considered include very different aspects: cerebrovascular and cardiometabolic factors, infections, and shift work [ 19 , 20 , 21 ]. One of the risk factors increasing the occurrence of insomnia is ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Immune system activation can result in disturbed sleep patterns, and conversely, abnormal sleep patterns can alter immune system efficacy. For example, observations have been reported linking COVID-19 to increased sleep disturbance and lower sleep quality ( 8 , 9 ). Chronic fatigue is also a common PASC-CVS symptom ( 8 , 9 ).…”
mentioning
confidence: 99%
“…For example, observations have been reported linking COVID-19 to increased sleep disturbance and lower sleep quality ( 8 , 9 ). Chronic fatigue is also a common PASC-CVS symptom ( 8 , 9 ). However, lower sleep duration has also been correlated with a greater risk of COVID-19 infection ( 10 ).…”
mentioning
confidence: 99%